500 digital illustration hints, tips, and techniques : the easy, all-in-one guide to those inside secrets for better image-making - Herriott, Luke; Gal, Hannah; Brandt, Robert; McCall, Jimm; Danaher, Simon (Mies, Switzerland ; Hove, UK : RotoVision, 2009)
Guides the reader from the basics of digital illustration through to advanced techniques, with sections on the commonly-used software programs, including Photoshop, Painter, Illustrator, Flash, Cinema 4D, and 3D Studio. This comprehensive handbook covers the essential technical considerations of digital illustration
Includes index.
MA
Keywords: Graphic arts; Computer drawing; Computer graphics